Pengembangan E-Book berbasis Kearifan Lokal pada Pembuatan Jamu Tradisional sebagai Literasi Kimia dengan Pendekatan Etno-STEM - Amtonis, Jesiyanti Suni; Sumarti, Sri Sulisogati; Wardani, Sri (Edukimia, 2022)
The low chemical literacy of students and chemistry teachers of SMA Negeri 1 Insana is due to not developing an electronic-based learning media. This study aims to develop an E-Book based on local wisdom on the manufacture of traditional herbal medicine as chemical literacy with an Ethno-STEM approach. The research method is 3D model R and D. Data collection techniques through interviews, validation and questionnaires. The instruments used in this study were validation sheets and questionnaire sheets. The E-Book was validated by two experts, namely material experts and media experts and the subjects in this study were ten students of class XI science at SMA Negeri 1 Insana. The results of the validity that have been analyzed obtained a material validation value of 84 percent and a media validation value of 92 percent so that the average percentage of expert validators on the product developed was 88 percent with very valid criteria, while the response of students on a small scale obtained a value of 75 percent with good criteria and large scale score of 90.66 percent with very good criteria. Based on the results of the study, it can be concluded that the developed E-Book was very valid and very good to use.